2005
DOI: 10.1002/cncr.20954
|View full text |Cite
|
Sign up to set email alerts
|

Cancer, Medicaid enrollment, and survival disparities

Abstract: BACKGROUND The current article examined survival for adults < 65 years old diagnosed with breast, colorectal, or lung carcinoma who were either Medicaid insured at the time of diagnosis, Medicaid insured after diagnosis, or non‐Medicaid insured. METHODS The authors hypothesized that subjects enrolling in Medicaid after they were diagnosed with cancer would explain disparate survival outcomes between Medicaid and non–Medicaid‐insured subjects. The authors used the Michigan Tumor Registry, a population‐based can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 19 publications
5
108
1
Order By: Relevance
“…As noted earlier, the review of the literature points to a lack of consistency among researchers relative to whether to exclude unstaged cases from the analysis [18,19,20], to group unstaged cases with latestaged cancers [21,22], or even to analyze unstaged cases in a separate stage category [11,14,23,24]. SEER reports survival rates for unstaged cases that are somewhat more favorable than for those with distant stage cancer, but less favorable than for those with regional stage cancer [3,4,5], and a previous study has documented differences in survival patterns among unstaged cases when analysis was performed in age-specific strata [11].…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, the review of the literature points to a lack of consistency among researchers relative to whether to exclude unstaged cases from the analysis [18,19,20], to group unstaged cases with latestaged cancers [21,22], or even to analyze unstaged cases in a separate stage category [11,14,23,24]. SEER reports survival rates for unstaged cases that are somewhat more favorable than for those with distant stage cancer, but less favorable than for those with regional stage cancer [3,4,5], and a previous study has documented differences in survival patterns among unstaged cases when analysis was performed in age-specific strata [11].…”
Section: Discussionmentioning
confidence: 99%
“…15,34,35,[42][43][44][45][46][47] Eight of these found that uninsured or Medicaid patients had worse health outcomes than privately insured patients. 15,35,[42][43][44][45][46][47] Of these, three were based on data from single states. Roetzheim et al, 35 15 Okunade et al 47 analyzed state-level data from 1990 to 1997 from a variety of sources, including the BRFSS; NCI's SEER registry; and the US Bureau of the Census.…”
Section: Studies Of Health Insurance and Cancer Outcomementioning
confidence: 99%
“…3 Studies examining health care outcomes related to insurance also find disparate outcomes; patients with inadequate insurance are more likely to have perforated appendicitis 4 and are more likely to die of cancer. 5 Intricate interrelationships among risk factors and a host of potential confounders make it difficult for researchers to attribute differences in outcomes to specific racial or insurance bias.…”
mentioning
confidence: 99%